HANDLING OF MINOR CRIMES OF THEFT IN OIL PALM PLANTATIONS - Rahman, Rojali; Munawar, Akhmad (Awang Long Law Review, 2024)
Palm oil plantations play a vital role in Indonesia's economy but face issues of palm fruit theft with losses valued under IDR 2.5 million. Since the implementation of Supreme Court Regulation (PERMA) No. 2 of 2012, such theft cases have been resolved through restorative justice (RJ), which has proven insufficient in providing a deterrent effect. Offenders frequently repeat their actions, resulting in economic losses for companies and social unrest in communities. This study evaluates the effectiveness of RJ in addressing minor theft cases in palm oil plantations in Tanah Laut, South Kalimantan. Using normative legal methods and case analysis, it was found that RJ often imposes lenient sanctions, such as signing statements or temporary confiscation of theft tools. This leniency motivates offenders to exploit legal loopholes without fear of serious consequences. Challenges in RJ implementation include social protection for offenders by village officials, limited supervision, and inadequate security personnel in vast plantation areas. The study recommends stricter sanctions, such as recording offenders’ criminal records in police databases to enhance deterrence. Strengthening collaboration between companies and law enforcement is also necessary to prevent repeated theft. The application of RJ in minor theft cases in palm oil plantations needs revision to be fairer and more effective in protecting companies, communities, and deterring offenders. This study aims to contribute to the development of more adaptive legal policies tailored to local needs.